2007
DOI: 10.1038/sj.ejcn.1602810
|View full text |Cite
|
Sign up to set email alerts
|

Association between decreased vitamin levels and MTHFR, MTR and MTRR gene polymorphisms as determinants for elevated total homocysteine concentrations in pregnant women

Abstract: Serum folate and MTHFR C677T and MTR A2576G gene polymorphisms were the determinants for tHcy levels. The interaction between low levels of serum Cbl and MTHFR (C677T or A1298C) or MTRR A66G gene polymorphisms was associated with increased tHcy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 45 publications
6
58
0
4
Order By: Relevance
“…It has been reported that although the common MTRR c.66 AϾG (p.I22M) missense mutation is not significantly associated with CHD in children, the homozygotes mutant G allele is associated with elevated plasma homocysteine concentrations in pregnant women. 20 However, to date, no studies of the possible correlation between variations in the noncoding region of MTRR and CHD have been published. In the present study, we have investigated polymorphisms in the noncoding region of the MTRR gene in 3 independent case-control studies with 2340 CHD cases and 2270 controls from the Han Chinese population.…”
Section: Clinical Perspective On P 490mentioning
confidence: 99%
“…It has been reported that although the common MTRR c.66 AϾG (p.I22M) missense mutation is not significantly associated with CHD in children, the homozygotes mutant G allele is associated with elevated plasma homocysteine concentrations in pregnant women. 20 However, to date, no studies of the possible correlation between variations in the noncoding region of MTRR and CHD have been published. In the present study, we have investigated polymorphisms in the noncoding region of the MTRR gene in 3 independent case-control studies with 2340 CHD cases and 2270 controls from the Han Chinese population.…”
Section: Clinical Perspective On P 490mentioning
confidence: 99%
“…Using gene-specific primers, DNA was PCR-amplified and restriction digested with specific enzymes, and examined for RFLPs of MTHFR (C677T & A1298C), CBS (844ins68 bp), MTR (A2756G) and RFC1 (G80A) (Chango et al, 2000;Dutta et al, 2005;Rai et al, 2006;Barbosa et al, 2008). The SNPs and the 68 bp insertion of CBS were resolved, respectively, on 3.5 and 2% agarose gels.…”
Section: Genetic Analysismentioning
confidence: 99%
“…Conflicting results of the studies on the relationship between the 1298A>C polymorphism and AIS, both in children and adults, can be found [12][13][14][15][16][17]. Previously, it was observed that the MTHFR 1298A>C polymorphism in combined analysis with the 677C>T polymorphism increased homocysteine levels as well as lowered plasma folate levels [18]. However, some studies do not confirm such a relationship [19].…”
Section: Introductionmentioning
confidence: 99%